Sapiens : a graphic history - Harari, Yuval N.; Harari, Yuval N.; Vandermeulen, David, 1968-; Vandermeulen, David, 1968-; Casanave, Daniel (Jonathan Cape, 2020)
The first volume of the full-color illustrated adaptation of his groundbreaking book, renowned historian Yuval Harari tells the story of humankind's creation and evolution, exploring the ways in which biology and history have defined us and enhanced our understanding of what it means to be 'human'.